Studying the Factors Affecting the Drag Coefficient in Non- Newtonian Fluids - A. R. Mohammed, Muhannad; Adil Elia Halagy, Dina (Iraqi Journal of Chemical and Petroleum Engineering, 2013)
The aim of this research is to study the factors affecting drag coefficient (C d ) in non-Newtonian fluids which are the rheological properties ,concentrations of non- Newtonian fluids, particle shape, size and the density difference between particle and fluid .Also this study shows drag coefficient (C d ) and particle Reynolds’ number (Re P ) relationship and the effect of rheological properties on this relationship. An experimental apparatus was designed and built, which consists of Perspex pipe of length of 160 cm. and inside diameter of 7.8 cm. to calculate the settling velocity, also electronic circuit was designed to calculate the falling time of particles through fluid. Two types of solid particles were used; glass spheres and crushed rocks as irregularly shaped particles with different diameters and compared with each other. The concept of equivalent spherical diameter (D S ) was used to calculate the diameters of irregularly shaped particles. The flow behavior for Non-Newtonian fluids was represented by Power-Law model. Two types of polymers were used, Carboxy Methyl Cellulose CMC with concentrations of (3.71, 5, 15 and 17.5) g/l and polyacrylamide with concentrations of (2, 4 and 6) g/l. The results showed that the drag coefficient decreased with increasing settling velocity and particle diameters and sizes; and increased as fluid become far from Newtonian behavior and concentrations and the density difference between particle and fluid. The results also showed that the rheological properties of Non-Newtonian fluids have a great effect on the drag coefficient and particle Reynolds number relationship, especially in laminar-slip regime and decreases or vanishes at transition and turbulentslip regimes. New correlations were obtained which relates drag coefficient with concentrations of polymers and with flow behavior indices for spherical and irregular shaped particles in Carboxy Methyl Cellulose CMC and polyacrylamide solutions.